Fine-needle aspiration biopsy of thyroid nodules: analysis of 61 cases - Torres, Orlando Jorge Martins (2002)
When a thyroid nodule is discovered, imaging alone is not usually sufficient to characterize the nodule as benign or malignant. Fine-neddle aspiration (FNA) of the thyroid gland has become the dominant method used to assess the need for resection of thyroid nodules. There are several reasons for nondiagnostic specimens including inadequate sampling, incorrect needle placement, inexperienced pathologists, and different diagnostic criteria among laboratories. The aim of the present study is to analyze the fine needle aspiration biopsy of the thyroid in patients who under went surgical resection. From January 1998 to December 2000, 61 fine needle aspiration biopsies were performed. Each cytology report was reviewed whit the corresponding surgical pathology, if resection had been performed. There were 56 female (91.8%) and 5 male (8.2%) patients ages ranging from 15 to 68 years (mean 37.6 years). Thirty aspirates were classified as benign, eighteen as follicular neoplasm, seven were malignant, and six were nondiagnostic. The results showed a sensibility of 81.2%, especificity of 69.2% and accuracy of 72.7%. Fine needle aspiration biopsy has high sensibility for malignant nodules and these patients should under go to surgical resection.